Effect Fake News for Democracy - Munadhil Abdul Muqsith; Valerii Leonidovich Muzykant (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThis paper aims to explain how fake news impacts democracy. This phenomenon is called the post-truth era. The development of information and communication technology is increasing the spread of information so that difficult to distinguish between true and false information. The research method uses normative juridical method, using secondary data obtained through literature study and qualitative analysis. The result and discussion of this research are serious threat from fake news for democracy, because it can cause social cohesion in the community. Some examples of how its impact on the world include the U.S. presidential election 2016, the Brexit referendum in the United Kingdom in 2016 and the 2017 French presidential election.Keywords: Fake News, Democracy, US Presidential Election, Brexit AbstrakMakalah ini bertujuan untuk menjelaskan bagaimana berita palsu berdampak pada demokrasi. Fenomena ini disebut era pasca-kebenaran. Perkembangan teknologi informasi dan komunikasi meningkatkan penyebaran informasi sehingga sulit untuk membedakan antara informasi yang benar dan yang salah. Metode penelitian menggunakan metode yuridis normatif, menggunakan data sekunder yang diperoleh melalui studi literatur dan dianalisis secara kualitatif. Hasil dan diskusi penelitian ini merupakan ancaman serius dari berita palsu untuk demokrasi karena dapat menyebabkan kohesi sosial di masyarakat. Beberapa contoh bagaimana dampaknya terhadap dunia termasuk pemilihan presiden Amerika Serikat 2016, referendum Brexit di Inggris pada tahun 2016 dan pemilihan presiden Prancis 2017.Kata kunci: Berita Palsu, Demokrasi, Pemilihan Presiden AS, Brexit АннотацияЦель этой статьи - объяснить, как ложные новости влияют на демократию. Это явление называется эрой пост-правды. Развитие информационных и коммуникационных технологий увеличивает распространение информации, поэтому трудно различить правдивую и ложную информацию. Данное исследование использует нормативно-юридический метод и вторичные данные, полученные в результате изучения литературы и проанализируемые качественным методом. Результаты и обсуждение этого исследования показывают, что ложные новости представляют серьезную угрозу для демократии, потому что они могут вызвать социальную сплоченность в обществе. Некоторые примеры того, какое влияние на мир оказывают президентские выборы 2016 года в США, Референдум Брексит в Великобритании в 2016 году и президентские выборы во Франции 2017 года.Ключевые слова: поддельные новости, демократия, президентские выборы США, Брексит